Aldehyde dehydrogenase-2 inhibition blocks remote preconditioning in experimental and human models - Contractor, H; Støttrup, N; Cunnington, C; Manlhiot, C; Diesch, J; Ormerod, J; Jensen, R; Bøtker, H; Redington, A; Schmidt, MR; Ashrafian, H; Kharbanda, R (2013)
Mitochondrial aldehyde dehydrogenase-2 (ALDH-2) is involved in preconditioning pathways, but its role in remote ischaemic preconditioning (rIPC) is unknown. We investigated its role in animal and human models of rIPC. (i) In a rabbit model of myocardial infarction, rIPC alone reduced infarct size [69 ± 5.8 % (n = 11) to 40 ± 6.5 % (n = 12), P = 0.019]. However, rIPC protection was lost after pre-treatment with the ALDH-2 inhibitor cyanamide (62 ± 7.6 % controls, n = 10, versus 61 ± 6.9 % rIPC after cyanamide, n = 10, P > 0.05). (ii) In a forearm plethysmography model of endothelial ischaemia-reperfusion injury, 24 individuals of Asian ethnic origin underwent combined rIPC and ischaemia-reperfusion (IR). 11 had wild-type (WT) enzyme and 13 carried the Glu504Lys (ALDH22) polymorphism (rendering ALDH-2 functionally inactive). In WT individuals, rIPC protected against impairment of response to acetylcholine (P = 0.9), but rIPC failed to protect carriers of Glu504Lys polymorphism (P = 0.004). (iii) In a second model of endothelial IR injury, 12 individuals participated in a double-blind placebo-controlled crossover study, receiving the ALDH-2 inhibitor disulfiram 600 mg od or placebo for 48 h prior to assessment of flow-mediated dilation (FMD) before and after combined rIPC and IR. With placebo, rIPC was effective with no difference in FMD before and after IR (6.18 ± 1.03 % and 4.76 ± 0.93 % P = 0.1), but disulfiram inhibited rIPC with a reduction in FMD after IR (7.87 ± 1.27 % and 3.05 ± 0.53 %, P = 0.001). This study demonstrates that ALDH-2 is involved in the rIPC pathway in three distinct rabbit and human models. This has potential implications for future clinical studies of remote conditioning. © 2013 Springer-Verlag Berlin Heidelberg.